A study of the Impact of online educational journals: The case of REDIE - Backhoff, Eduardo; Rentería, Rosalinda; López-Ornelas, Maricela; Vidaurri, Gabriela (Education Policy Analysis Archives, 2011)
The main purpose of this study was to determine the academic impact the Online Journal of Educational Research (REDIE) has had in the course of its first ten years of life (1999-2009). The journal was studied in terms of the number, type and source of citations of its articles, as well as the ongoing use of the references based on each article published during this period. Since REDIE is not indexed in the database of the Web of Science of Thomson Reuters (ISI, by its former acronym in English), the examination of its impact was based on quotes from open publications found in cyberspace. The search engines Google and Google Scholar looked for citations of 161 articles; the results are analyzed in terms of how often the REDIE was quoted, the type of documents that cited its articles, the home countries of the sources cited, and the behavior of the citations over time. We concluded with a summary of findings, and a comparison of citation indicators of REDIE with six Latin American journals in education and psychology.